"Perrotta-Marciano questionnaire on the grade of awareness of one's deviant and criminal behaviors" (ADCB-Q-2) and the "Criminal spectrum": Development, Updates, Regulation, and Validation of a new psychometric instrument - Giulio Perrotta; Antonio Marciano; Domenico Piccininno (Annals of Psychiatry and Treatment - Peertechz Publications, 2023)
Introduction: Absent in the literature is the category of "criminal spectre" as a macro container that includes all those deviant, antisocial, and psychopathic behaviors, thereby generating confusion and interpretative distortions, as in the case of antisociality and psychopathy among them considered in some cases as synonyms.  Methods: Updated the Perrotta-Marciano Questionnaire on the state of awareness of one's deviant and criminal behaviors (ADCB-Q), from 30 items to 40 items and with 2 subscales to differentiate deviant from antisocial behaviors (ADCB-Q-2), to make comparisons with the Deviant Behavior Variety Scale (DBVS) and the Hare Psychopathy Checklist-Revised (PCL-R).  Results: Statistical analysis showed that the second edition of the test has a well-defined and stable construct (R = 0.999; p ≤ 0.001), and is positively correlated with the other 2 compared tests, the DBVS (R = 0.943) and the PCL-R (R = 0.966). A comparison of comparable items returned an R = 0.999 with a 99.9% equal value.  Conclusion: Defining the "criminal spectre" as a dysfunctional pattern consisting of a clinically relevant cross-cutting condition in which the subject manifests deviant, borderline, histrionic, narcissistic, antisocial, and psychopathic behaviors, the Perrotta-Marciano Questionnaire on the State of Awareness of One's Deviant and Criminal Behaviors (ADCB-Q-2) is a valid, efficient, effective and stable psychometric tool to identify in behavioral profiles all the behaviors that fall within the "criminal spectrum".